2013
DOI: 10.1007/s10834-013-9378-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Child Behaviour Problems on Maternal Employment: A Longitudinal Cohort Study

Abstract: This prospective population-based study examined associations between children’s behaviour problems and maternal employment. Information on children’s behaviour problems at 3 years from 22,115 mothers employed before pregnancy and participating in the Norwegian Mother and Child Cohort Study were linked to national register data on employment and relevant social background factors, mothers’ self-reported susceptibility to anxiety/depression and mother-reports of day-care attendance and fathers’ income. Mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
(85 reference statements)
3
16
0
Order By: Relevance
“…However, the effects are more pronounced among the mothers, and the sickness absence differences between the two groups of mothers are particularly large during the two first years after birth. This finding is consistent with previous research demonstrating that the birth of a child with a chronic illness or disability influences maternal health negatively (Burton et al, 2008;Nes et al, 2014). Moreover, the results are also in line with a Norwegian study (Wendelborg and Tøssebro, 2015), which found higher sickness absences among parents caring for a disabled child, and that mothers were particularly affected.…”
Section: Discussionsupporting
confidence: 92%
“…However, the effects are more pronounced among the mothers, and the sickness absence differences between the two groups of mothers are particularly large during the two first years after birth. This finding is consistent with previous research demonstrating that the birth of a child with a chronic illness or disability influences maternal health negatively (Burton et al, 2008;Nes et al, 2014). Moreover, the results are also in line with a Norwegian study (Wendelborg and Tøssebro, 2015), which found higher sickness absences among parents caring for a disabled child, and that mothers were particularly affected.…”
Section: Discussionsupporting
confidence: 92%
“…However, the present study suggests that the availability of quality child care options and decentralization of special education services do not eliminate the excess risk of maternal work absence due to children's language impairments. This is also in line with findings from a previous study based on the MoBa cohort, which showed that previously employed mothers of children with behavior problems are at risk of leaving paid employment by child age 3 years (Nes et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, on the basis of previous research on caregiving, health, and employment, we predicted lower employment and higher sick leave rates among mothers who reported language impairment in their child. We expected the risk to be higher for co‐occurring problems given that behavior problems have been shown to be particularly closely related to mothers' caregiving strains (King et al, ; Raina et al, ) and to constitute a barrier to paid employment in mothers of preschool‐age children (Nes et al, ). We also hypothesized that differences in work absence between groups of mothers remain or increase, given that language impairment generally persists and is associated with social, emotional, and academic problems that often become more pronounced with age.…”
Section: Language Impairment and Maternal Work Absencementioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been some longitudinal research, 3 , 15–17 there is very little European evidence 9 , 10 , 18 . In order to investigate these two potential mechanisms, we used longitudinal data from Millennium Cohort Study, a large, contemporary cohort of UK children born in 2000, with information on childhood long-term limiting illness and maternal employment recorded in early to middle childhood.…”
Section: Introductionmentioning
confidence: 99%